EVALUATING WHAT MATTERS: STUDENT PERSPECTIVES ON PEER EVALUATION IN COOPERATIVE LEARNING - Han, Shin-Il; Son, Hyesook (International Online Journal of Education and Teaching, 2025)
This study investigates the criteria college students prioritize in peer evaluation within cooperative learning environments, aiming to establish a student-centered evaluation framework to enhance team effectiveness and learning outcomes. Utilizing a phenomenological approach, one of the qualitative research methods, 25 students from an education-related course at a Korean university were sampled for this study with creating and weighting peer evaluation criteria based on their experiences in team-based problem-solving tasks. From their criteria responded, seven primary categories emerged, including task preparation and completion, problem-solving skills, diligence and attendance, responsibility in role performance, communication, proactiveness and contribution, and creativity and originality. Findings indicate that responsibility and trust are fundamental to effective collaborative learning. This study contributes to understanding peer assessment’s role in fostering teamwork, with recommendations for integrating responsibility-driven evaluation criteria in colleges and universities.